2018
DOI: 10.3390/app8020247
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a Direct to an Indirect Refrigeration System at Medium Temperature Using R-134a and R-507A: An Energy Impact Analysis

Abstract: This work presents the experimental evaluation of energy consumption and refrigerant charge reduction when a commercial direct expansion refrigeration system is converted into an indirect system. The evaluation (with R-134a and R-507A) used a commercial cabinet with doors for medium temperature and a single-stage refrigeration cycle using a semi-hermetic compressor and electronic expansion valve; 24-h energy consumption tests were performed at laboratory conditions for each refrigerant and configuration at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Sánchez et al [8], measured energy increments up to 14.0% when reconverting a R134a/CO 2 direct cascade to an indirect one using propylene-glycol at medium temperature. Llopis et al [9], presented an experimental evaluation of energy consumption reconverting a direct expansion refrigeration system to an indirect system, using R134a and R507A, with energy consumption increases up to 22.8% (R134a) and 38.7% (R507A).…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez et al [8], measured energy increments up to 14.0% when reconverting a R134a/CO 2 direct cascade to an indirect one using propylene-glycol at medium temperature. Llopis et al [9], presented an experimental evaluation of energy consumption reconverting a direct expansion refrigeration system to an indirect system, using R134a and R507A, with energy consumption increases up to 22.8% (R134a) and 38.7% (R507A).…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [8] and Hu et al [9] presented the optimum design and a prediction model of heat exchangers. Other studies [10][11][12][13] reported various approaches for improving efficiency and to mitigate GHG emissions. All these studies are indispensable for continuous progress, and guarantee steady steps toward reducing direct and indirect emissions of GHGs.…”
Section: Fundamental Process Components and Mechanical Vapor Comprementioning
confidence: 99%
“…This arrangement allows reducing substantially the refrigerant's leak rate up to 90% [17] as well as the amount of refrigerant used in the system [18]. However, indirect layout uses a fluid pump and an additional heat exchanger that increases the energy consumption of the refrigerating facility due to the power consumed by the pump and the extra temperature difference required in the secondary fluid cooler [19][20][21].…”
Section: Introductionmentioning
confidence: 99%